A geological overview of the limestone members of the Woyla Group of Sumatra, Indonesia - Muhammad Ridha Adhari; Rahmat Hidayat (UIR PRESS, 2023)
Mesozoic limestone units of the Woyla group were identified in many places across the northern part of Sumatra, Indonesia. Even though these sedimentary rocks may play an important role as an element of the potential Pre-Tertiary hydrocarbon play of Sumatra, their characteristics are still not well understood. This study tries to fill this research gap and aims to better understand the characteristics of the limestone members of the Woyla group. There are three objectives of this study: (1) to characterise structural features, and deformation of the Woyla Group; (2) to provide sedimentary characteristics of the limestone members of the Woyla Group; and (3) to understand the main influences on the development of the limestone members of the Woyla Group. An integrated geological analyses, including structural scanline analysis, petrographic analysis, and acid digestion analysis, was conducted to achieve the objectives of this study. Findings from this research show that the limestone members of the Woyla group were strongly deformed, and structural features such as bedded strata, faults, folds, and joints were identified within these rocks. The limestone units of the Woyla group consist of at least six microfacies. These are wackestone, packstone, wackestone-packstone, packstone-rudstone, fossiliferous sandstone, and fossiliferous shale. Depositional processes, sea level fluctuations, tectonisms, and climatic variations are interpreted as the main factors influencing the development and evolution of these limestone units. It is expected that the results of this study could advance our understanding of the Pre-Tertiary carbonate rocks in general, and the Woyla group of Sumatra in particular.